The Authority of Government Officials in Delegating and Mandating - Arifin Tumuhulawa; Roy Marthen Moonti (Unnes Law Journal, 2021)
Power sharing vertically in a unitary state has its consequence for the existence of the environment of both central and local governments. By the existence, another consequence appears which is the relationship between central government and local government in order to avoid the overlap of the authority implementation. One of the crucial aspects in democratic state of law (democratischerechtsstaat) is legality principle (legaliteitsbeginsel). It means that each legal action of the government should be based on the applicable laws and regulations or the authority given by the applicable regulations. The problem statements and the aims of this research are to find out the authority of the Government Officials in running the government affairs and to investigate the meaning of delegating and mandating conducted by the government officials. Authority is the formal power owned by administration boards and/or officials or other state administrators to act in public law report including some competences. The basic principles of authority are first, the administration officials act and make decision based on their authority; second, the authority to use should be accounted for and tested by both legal norm and legal principle. Delegation is defined as delegating authority from the higher board and/or government officials to the subordinates in which the responsibility and liability is switched completely to the delegates. Mandate does not contain the transfer of authority. It is only the mandator gives his/her authority to another person (mandatary) to make decision or take actions on his/her behalf.